Clinical And Laboratory Indicators and Quality of Life in Liver Cirrhosis - Zaripov Z.O; Rakhmatullayeva G.K; Khudayberganova N.H (Peerian Journals Publishing, 2023)
In this article, study clinical laboratory indicators in relation to quality of life in patients with liver cirrhosis of various etiologies.
Keywords: cirrhosis; clinical; indicators